2016
DOI: 10.3168/jds.2015-10400
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of pasteurized milk on expiration date in Tehran, Iran

Abstract: The aim of this study was to determine the microbiological quality of pasteurized milk on expiration date in Tehran. Two hundred fifty-four samples collected using a simple randomized sampling method from March 2014 to January 2015 were tested for total microbial count, coliform count, and Escherichia coli contamination according to Iran's National Standards methods. Total microbial count, coliform count, and E. coli contamination exceeded the standard limits in 61.1% [>7.5 × 10(4) (4.88 log) cfu/mL], 24.4% [>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In this study, the values of the TPC for the unfinished UHT milk had exceeded the maximum values starting from 25°C for 2 hours (6.05 log 10 CFU/mL). Koushki et al, (2016) stated that total microbial count of pasteurised milk on an expired date is 4.88 log 10 CFU/mL. Interestingly, TPC value of UHT milk at 15°C in 4 hours (4.85 log 10 CFU/mL) shows in Figure 2 is close to the value of microbial growth for expired date milk.…”
Section: Resultsmentioning
confidence: 64%
“…In this study, the values of the TPC for the unfinished UHT milk had exceeded the maximum values starting from 25°C for 2 hours (6.05 log 10 CFU/mL). Koushki et al, (2016) stated that total microbial count of pasteurised milk on an expired date is 4.88 log 10 CFU/mL. Interestingly, TPC value of UHT milk at 15°C in 4 hours (4.85 log 10 CFU/mL) shows in Figure 2 is close to the value of microbial growth for expired date milk.…”
Section: Resultsmentioning
confidence: 64%
“…While the humidity recorded a decrease of 63, 66 and 63% at the same concentrations for the eleventh day compared to the control sample which amounted to 38%. Through the results, it was found that there was a decrease in moisture levels with an increase in the duration of cryopreservation, and that this decrease can be due to the decomposition of meat tissues by proteolytic enzymes, which directly affects the change in the pH of the meat, and thus exudes a section of free water to the outside of the tissues and also affects the holding power of water in the tissues, as well as the evaporation of part of the moisture when associated with a decrease in relative humidity in the conditions surrounding the cold storage [39] reported that fresh lamb moisture was 75.16% and 75.07% decreased after a five-day period of cryostorage at 5°C. It was also shown through the results that the pH increased with the progress of the storage period in kebab meat manufactured from chicken thigh and stored by refrigeration, as the increase and variation in pH are associated with the deterioration of proteins and the release of amino acids and the formation of ammonia, nitrogenous bases and amines during tissue decomposition during storage, and the results of the study are consistent with what [40] said, as they explained that many of the qualitative qualities of meat begin to decline when the pH value reaches more than 6.20, and this may be Caused by an increase in nitrogenous bases and amino acids resulting from protein breakdown by proteolytic microorganisms [41].…”
Section: Staphylococcus Epidermidis and Pseudomonas Aeruginosamentioning
confidence: 99%
“…Several studies have investigated the microbial quality of milk and its products through the world; in Egypt (Ahmed et al, 2014;Abbas et al, 2016), in Saudi Arabia (Al-Otaibi, 2009, in Sri Lanka (Deshapriya et al, 2006), in Iran (Koushki et al, 2015); in South Africa (Karzis et al, 2018), in Korea (Ryu et al, 2021), in India (Mallappa et al, 2021), andin Tunisia (Dabbabi et al, 2018;Fitouhi et al, 2018;Klibi et al, 2018). However, in Sfax region, Tunisia, a limited number of investigated samples in few studies have considered the microbial contamination of UHT (tetra-pack packaging) and pasteurized milk, as well as its fermented products (Samet-Bali et al, 2016).…”
Section: Introductionmentioning
confidence: 99%